Matrix effect of swine urine on time-resolved fluorescent nanobeads and colloidal gold immunochromatographic assay - Yong Zhang (Taylor & Francis Group, 2018)
Immunochromatographic assay (ICA) is an efficient analytical technique and rapid, convenient, easy-to-use, low-cost, and on-site detection method that has been widely used to evaluate food safety. However, an important issue to be addressed for this method is its matrix effect. In this work, time-resolved fluorescent nanobead ICA (TRFN-ICA) and colloidal gold ICA (CG-ICA) were developed to detect clenbuterol in swine urine. Under optimized working conditions, the limits of detection of TRFN-ICA and CG-ICA were 16 and 68 pg/mL, respectively. The matrix effect on TRFN-ICA and CG-ICA was assessed in 20 swine urine samples. Results indicated that the sensitivity of TRFN-ICA was better than that of CG-ICA, and the detection time of the former was shorter than that of the latter. The matrix effect on TRFN-ICA was more serious than that on CG-ICA.